Pathogenic Variant Rs1471414348of the TTN Gene in the Patient with Familial Left Venticular Noncompaction Cardiomyopathy - O. V. Kulikova; A. N. Meshkov; R. P. Myasnikov; A. V. Kiseleva; S. N. Koretsky; A. A. Zharikova; M. S. Kharlap; E. A. Mershina; V. E. Sinitsyn; O. P. Skirko; I. A. Efimova; M. S. Pokrovskaya; et al. (Рациональная фармакотерапия в кардиологии, 2019)
The clinical, instrumental and molecular-genetic studies for proband and family members for identification of family form of left ventricular noncompaction cardiomyopathy (LVNC) presented in the article. According to the results of the examination, the diagnosis LVNC was made. Drug therapy was adjusted, and a cardioverter defibrillator was implanted for the primary prevention of sudden cardiac death. Given the hereditary nature of the disease, family screening was conducted. By the family screening the disease was diagnosed in the mother of proband. Later, was made exome sequencing in a group of genes related to the development of left ventricular noncompaction cardiomyopathy. One likely pathogenic variant (rs1471414348, stop codon) in the TTN gene was detected. The discovered variant was validated by Sanger sequencing and was detected only in the proband and his mother, and was absent in other relatives. There were no other pathogenic and probably pathogenic variants in genes associated with the development of left ventricular noncompaction and other cardiomyopathies. As a result of family screening the new cases were diagnosed, the pathogenic variant of the TTN gene was identified, that is probably responsible for the development of the LVNC phenotype.